Galenic Preparations of Therapeutic Cannabis sativa Differ in Cannabinoids Concentration: A Quantitative Analysis of Variability and Possible Clinical Implications - Alessandra Bettiol; Alessandra Bettiol; Niccolò Lombardi; Niccolò Lombardi; Giada Crescioli; Giada Crescioli; Valentina Maggini; Valentina Maggini; Eugenia Gallo; Eugenia Gallo; Alessandro Mugelli; Alessandro Mugelli; et al. (Frontiers Media S.A., 2019)
Introduction: Magistral preparations of therapeutic cannabis are extracted from standardized products imported from Holland or from the Florence Military Pharmaceutical Chemical Works, but extraction protocols differ among galenic laboratories. This study assessed the inter-laboratory variability in concentrations of cannabidiol (CBD), cannabinol (CBN), tetrahydrocannabinol (THC), and tetrahydrocannabinolic acid (THCA) among different magistral oil preparations.Methods: 219 samples of Bediol, Bedrobinol, Bedrolite or FM-2 70 or 100 mg/ml in oil were collected from 3 laboratories. Concentrations of CBD, CBN, THC, and THCA were quantified by high-pressure liquid chromatography; inter-laboratories variability was assessed using the Kruskal-Wallis test.Results: A significant variability in CBD and THC concentrations was found for Bediol 70 mg/ml samples from 2 laboratories [for CBD: median 5.4 (range 4.8-6.6) vs. 6.1 (4.9-7.2) mg/ml, p = 0.033; for THC: 3.6 (3.1-3.9) vs. 4.0 (2.6-5.1) mg/ml, p = 0.020]. As for Bediol 100 mg/ml, a significant variability emerged in THC concentrations among the three considered laboratories [5.7 (-) vs. 4.2 (1.5-4.8) vs. 5.2 (4.2-6.9), p = 0.030]. No significant inter-laboratory variability emerged for Bedrocan and Bedrolite. Concentrations of CBD, CBN, and THC were <LOQ in all Bedrocan samples, and CBN and THCA were <LOQ in all Bedrolite samples. As for FM-2, a significant inter-laboratories variability was found for CBD concentrations.Conclusion: Quantitative variability of cannabinoids in magistral preparations might impact on the efficacy and safety of therapeutic cannabis. A standardized protocol is needed to guarantee a homogeneous product and patients' therapeutic continuity.